Bromine precursor mediated synthesis of shape controlled cesium bromide nanoplatelets and their mechanism study by DFT calculation - Noh, Jae Young; Baek, Seungmin; Park, Ju Hyun; Kwak, Sang Kyu; Kim, Sang Wook (Inorganic Chemistry, 2020)
We synthesized CsBr nanoplatelets and controlled their size and shape using HBr and tetrabutylammonium bromide (TBAB) as bromine precursors, obtaining hexagonal and rectangular plates, respectively. The phenomena were elucidated by density functional theory calculations, which indicated that the formation of the hexagonal shape was explained by comparing the relaxed surface free energy of oleate on the exposable surfaces of the CsBr plates. As the bromine precursor changed from HBr to TBAB, the formation of the rectangular shape was determined by comparing the surface free energy and attachment free energy between exposable surfaces due to its bulky surfactant tail. In addition, the TEM measurements indicated that the rectangles or hexagonal shapes are aligned precisely regardless of their size. The data mean that the large plates split into smaller plates as the temperature increases so that the nanoplatelets were formed by a top-down method in which a large plate was split by surfactants rather than through a bottom-up method in which a rectangle or a hexagon grew from smaller particles. The facts were explained by the surface chemical thermodynamics model which showed that the surface area (σ) and the crystal size decreased as the temperature increased.
Keywords: Bottom up methods; Mechanism studies; Rectangular plates; Rectangular shapes; Surface chemicals; Surface free energy; Temperature increase; Tetrabutylammonium bromide